Pengaruh Jumlah Uang Beredar dan Tingkat Suku Bunga serta Pengeluaran Pemerintah terhadap Inflasi di Indonesia - Agusmianata, Nuri; Militina, Theresia; Lestari, Diana (Faculty of Economics and Business Mulawarman University, 2017)
Effect of Money Supply and Interest Rates and Government Expenditures to Inflation in Indonesia..This study aims to determine the effect of the money supply, interest rates and government expenditures to inflation in Indonesia. Theory used the theory of Irving Fisher, Gibson Paradox theory and the theory of Keynes. The study was conducted by using multiple linear regression analysis tool Cobb-Douglas function. Hypothesis testing using t test and F test is used to determine the feasibility of the model.The analysis revealed a significant effect of money supply on inflation, interest rates have a significant effect on inflation and government expenditures significant effect on inflation. The money supply affects most to inflation in Indonesia.Keywords: Money Supply, Interest Rates, Government Expenditures and Inflation